The Efficiency Analysis of Islamic Commercial Banks Using a Two-Stage Data Analysis Method: Efficiency Analysis - Tri Annisya; Nurbaiti Nurbaiti (Institute for Research and Community Empowerment (LPPM TAZKIA), 2022)
A measure of company efficiency is also commonly used in banking. The DEA (Data Envelopment Analysis) method, which compares the input and output, is a mathematical program optimization method. This study investigates the efficiency level of Islamic banks in Indonesia from 2018 to 2021. It examines the role of capital and liquidity and their impact on Islamic banking efficiency. The quantitative methods used were nonparametric methods (DEA) and parametric methods using Tobit regression methods to examine capital and liquidity effects. The results show that Indonesia's Islamic Commercial Bank (BUS) is not operating effectively, according to the DEA's average efficiency score of 0.911 from 2018 to 2021. Furthermore, the findings suggest that capital and liquidity can improve the efficiency of Indonesian Islamic commercial banks. Keywords: Efficiency, Islamic Commercial, Two Stage DEA, Tobit Model